Increased Human Interleukin-32 Expression Is Related to Disease Activity of Graves' Disease - Yao, Qiuming; Wang, Bin; Jia, Xi; Li, Qian; Yao, Wei; Zhang, Jin-an (Frontiers in Endocrinology, 2019)
Recently, abnormal expression of interleukin-32 (IL-32) has been involved in various inflammatory or autoimmune diseases. But the knowledge about the expression of IL-32 in Graves' disease (GD) is still unknown. This study is aimed to explore the human IL-32 expression in GD and the association of IL-32 expression with the disease activity of GD. A total of 125 GD patients and 97 normal controls (NC) were recruited in this study. We examined IL-32 mRNA level in peripheral blood mononuclear cells (PBMCs) of 43 GD patients and 41 controls using real-time polymerase chain reaction (RT-PCR). Serum IL-32 level of 40 GD patients and 34 controls was measured by enzyme linked immunosorbent assay (ELISA). In another cohort including 42 GD patients and 22 controls, we detected the percentages of IL-32α+ cells, CD4+IL-32α+T cells and CD4-IL-32α+ cells in PBMCs by flow cytometry. In GD patients, IL-32 mRNA expression was dramatically higher than that in controls (P<0.001) and positively associated with FT3 (P=0.036, r=0.321). Subgroup analysis revealed that the IL-32 mRNA level was elevated in both newly onset GD and refractory GD group (P<0.01, P<0.001 respectively) compared with controls. Furthermore, in refractory GD group, the IL-32 mRNA expression was also positively correlated with FT3 (P=0.019, r=0.560). In addition, serum IL-32 level was notably higher in GD patients than that of controls (P<0.01). Subgroup analysis also indicated that serum IL-32 level in both newly onset GD and refractory GD group was higher in comparison with controls (P=0.015, P=0.023 respectively) and serum IL-32 level in refractory GD patients correlated with TRAb positively (P=0.043, r=0.481). The percentages of IL-32α+ cells, CD4+IL-32α+ T cells, and CD4-IL-32α+ cells were all significantly enhanced in GD patients compared with controls (P=0.005, P=0.017, P=0.016 respectively). IL-32 and IL-32α+ cells may be associated with the pathogenesis of GD. IL-32 may become a promising target for the treatment of GD